Evaluation of foot postures of assistant refereesin the regional football league - (:unkn) unknown (My University, 2019)
Purpose: The aim of this study was to investigate the physical activity status, foot postures and plantar pressure distributionsof football assistant referees in the Istanbul Regional League, who presented with the complaint of calf pain.Methods: A total of fifteen assistant referees (mean age: 21.00±1.9 years) and 15 healthy subjects (mean age: 21.53±0.8years) were included the study. The participants' physical activity levels were evaluated with the Short Form of theInternational Physical Activity Questionnaire (IPAQ-SF), foot posture was examined with the Foot Posture Index-6 (FPI-6) andpedobarographic examinations were performed with the Novel EMED-xR.Results: There was a statistically significant difference between the referee group and the control group in two sub parametersof the IPAQ-SF which were total physical activity MET- min/wk, vigorous MET- min/wk (p=0.044, p=0.002, respectively). Inpedobarographic evaluation, there was not a statistically significant difference between the referee and control groups inmaximum force and peak pressure of any area of the foot. Also, there was not a statistically significant difference in FPI-6 test.Conclusion: The present study results showed that side running did not change the foot posture in assistant referees. It wasdetermined that calf pain, which could not be affected due to a physical cause, was not associated with foot posture. Wesuggest that future studies should examine sports field, the sports equipment and other factors related pain to determine thecause of pain.

Amaç: Bu çalışmanın amacı, baldır ağrısı şikayeti ile kliniğe başvuran İstanbul Bölge Ligi futbol yan hakemlerinin ayak postürlerinin, fiziksel aktivite durumlarının ve ayak taban basınç dağılımlarının incelenmesi idi. Yöntem: Çalışmaya toplam 15 yan hakem (ortalama yaş: 21,00±1,9 yıl) ve 15 sağlıklı birey (ortalama yaş: 21,53±0,8 yıl) dâhil edildi. Katılımcıların fiziksel aktivite düzeyleri Uluslararası Fiziksel Aktivite Anketi'nin (IPAQ-SF) kısa formu ile, ayak postürleri Ayak Postür İndeksi-6 (FPI-6) ile değerlendirildi. Pedobarografik incelemeler Novel EMED-x Rile ile yapıldı. Bulgular: Hakem grubu ile kontrol grubu arasında IPAQ-SF'nin fiziksel aktivite metabolik eşdeğer dakika/hafta (MET-dk/hf), kuvvetli MET-dk/hf alt parametrelerinde iki grup arasında istatistiksel olarak anlamlı farklılık vardı (sırasıyla; p=0,044, p=0,002). Pedobarografik değerlendirmede, hakem ve kontrol grupları arasında, ayağın herhangi bir bölgesinin maksimum kuvvet ve pik basınç değerlerinde istatistiksel olarak anlamlı bir fark yok idi. Ayrıca, FPI-6 testinde istatistiksel olarak anlamlı bir fark yok idi. Sonuç: Bu çalışma, yardımcı hakemler tarafından yapılan yan koşuların ayak postürünü değiştirmediğini göstermiştir. Fiziksel bir nedeni saptanamayan baldır ağrısının ayak postürü ile ilişkili olmadığı belirlendi. Gelecekte yapılacak çalışmalarda ağrının nedeniyle ilgili olarak spor alanının, kullanılan spor malzemelerinin ve ağrıya yol açabilecek diğer faktörlerin ayrıntılı incelenmesini önermekteyiz.
Bölgesel futbol ligindeki yardımcı hakemlerin ayak postürlerinin değerlendirilmesi